2020
DOI: 10.1108/mrjiam-06-2020-1053
|View full text |Cite
|
Sign up to set email alerts
|

Understanding employee responses to COVID-19: a behavioral corporate social responsibility perspective

Abstract: Purpose The purpose of this study is to critically synthesize and integrate conceptual and empirical research on the behavioral perspective on corporate social responsibility (CSR) and explain why it is useful and necessary, especially in the wake of the COVID-19 pandemic. The authors explain why CSR can result in both positive and negative outcomes and provide future research directions and recommendations for practice and policymaking. Design/methodology/approach This study focuses on critical literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 68 publications
2
124
0
14
Order By: Relevance
“…Horizontal restrictions might work in theory but will induce different local responses in practice because of the underlying social differences. Besides mobility limitations, adequate economic incentives [29, 30] and behavioral nudging [31, 32] should be implemented to maintain high levels of compliance, while additional strategies should be devised and implemented locally to protect individuals who can not afford to comply with mobility restrictions [33, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal restrictions might work in theory but will induce different local responses in practice because of the underlying social differences. Besides mobility limitations, adequate economic incentives [29, 30] and behavioral nudging [31, 32] should be implemented to maintain high levels of compliance, while additional strategies should be devised and implemented locally to protect individuals who can not afford to comply with mobility restrictions [33, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, this paper only investigated the mediating role of OC in explaining the CSR–OP link. However, it is important to consider that various important micro-level variables (e.g., meaningfulness of work, work engagement, motivation, thriving, vigor, and psychological well-being) are likely to function as a critical intermediating channel to translate the positive influence of CSR activities into organizational performance [ 8 , 9 , 10 , 11 , 12 , 13 ]. In future studies, this issue should be fully dealt with.…”
Section: Discussionmentioning
confidence: 99%
“…These inconclusive results call for more work on the CSR–performance link. Against this backdrop, some previous studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] have suggested that future work on CSR needs to elaborate on the underlying processes (e.g., mediators and moderators) of the relationship to resolve the inconclusiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Aguinis et al [40] provided a theoretical work about CSR and employee volunteerism regarding the COVID-19 pandemic. Unfortunately, some companies began facing reduced commitment from workers as they questioned unsafe working conditions, for example, lack of adequate protective equipment or working with positively tested colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…When an employee is not involved or aware of CSR strategy (does not believe in it or handles it ineffectively) then his or her personal social action will also be rare. Aguinis et al [40] argued that the so-called peripheral CSR could cause many troubles when the employees do not find meaningfulness through their work (i.e., lack of sensemaking and integration of the CSR strategy into a firm's routine and activities). The opposite of this and a kind of solution is embedded CSR, which relies on the company's core competencies, and in this way results in positive outcomes for employees, as well.…”
Section: Literature Reviewmentioning
confidence: 99%